Evaluation of the National Urban Community Empowerment Program - Suparno, Suparno (Komunitas, 2019)
The main problem in this study is the low level of community participation in the implementation of National Urban Community Empowerment Program (NUCEP) in Grobogan Regency. This can be seen from the lack of community involvement in the entire process of the activity stage. The purpose of this study was to find out how the level of community participation in the implementation of NUCEP in Grobogan Regency. This research method uses a qualitative descriptive approach. Data analysis used qualitative and tirangulasi data analysis techniques. The evaluation model used is the Context, Input, Process and Product. The evaluation results show that the implementation of NUCEP is good, the context of the implementation of NUCEP is good, the input of NUCEP is good, but the available funds are insufficient to meet community needs; the implementation process went well, at the stage of preparation for less community participation especially in the FGD on Reflections on Poverty and the Preparation of Medium-Term Planning for Poverty Reduction Programs; then the implementation of the activities went well and the products of the NUCEP activities in the form of physical activities benefited the community. Based on the evaluation results it is recommended that, the effectiveness of NUCEPÂ  needs to be increased, the NUCEP District apparatus must be more democratic and participatory in the implementation of planned programs. Community involvement must always be encouraged in all processes and stages of activities, starting from planning, implementation, monitoring and evaluation, and in the preparation of reporting for each activity.